ASTARLOA, Ignacio (Dir.) (2015). Memento Práctico de Técnica Normativa. Madrid: Ed. Francis Lefebvre (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2016)
Recensión de la obra: ASTARLOA, Ignacio (Dir.) (2015). Memento Práctico de Técnica Normativa. Madrid: Ed. Francis Lefebvre.